PENGEMBANGAN PERMAINAN DADU REWARD BERBASIS INKUIRI UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH ANAK USIA 5–6 TAHUN - Tsalitsa Rifdah Sumayyah; Eka Cahya Maulidya; Kartika Rinakit Adhe; Yes Matheos Lasarus Malaikosa (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to develop and validate a reward dice game learning media based on an inquiry learning model to improve problem-solving skills in children aged 5–6 years. The research method used is Research and Development (R&D) with the ADDIE development model which includes the stages of analysis, design, development, implementation, and evaluation. The resulting product is a reward dice game media equipped with a challenge book, game rules, and rewards as positive reinforcement, which are designed according to the characteristics of early childhood development and inquiry syntax. This research was conducted at Aisyiyah Bustanul Athfal 1 Banjarjo Kindergarten, Bancar, Tuban with group B children aged 5–6 years as subjects. The validation results showed that the reward dice game media was in the very valid category, with a feasibility percentage of 100% from material experts and 97,5% from media experts. Data analysis used a descriptive quantitative approach, while the reliability test of the observation instrument showed a value (α = 0,900). The results of limited trials showed that the use of reward dice games was able to increase children's active involvement, focus, and courage in solving problems. Thus, inquiry-based reward dice game media is considered suitable for use as an alternative effective and meaningful learning media for early childhood.